2006
DOI: 10.1017/s0022112006009980
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically controlled multi-scale flows

Abstract: We generate a class of multi-scale quasi-steady laminar flows in the laboratory by controlling a quasi-two-dimensional shallow-layer brine flow by multi-scale Lorentz body forcing. The flows' multi-scale topology is invariant over a broad range of Reynolds numbers, Re 2D from 600 to 9900. The key multi-scale aspects of this flow associated with its multi-scale hyperbolic stagnation-point structure are highlighted. Our multiscale flows are laboratory simulations of quasi-two-dimensional turbulent-like flows, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 44 publications
3
64
1
Order By: Relevance
“…[6] showed that the number density n s of stagnation points is a power-law function of the outer to inner length-scale ratio L/η, n s = C s L −d (L/η) Ds where the fractal dimension D s is such that p + 2D s /d = 3 and d=2, 3 for 2D, 3D turbulence. [13] generated a Q2D multi-scale laminar flow with an imposed multi-scale spatial distribution of stagnation points and corroborated that such a flow has a powerlaw energy spectrum in agreement with p + D s = 3. The same rig and family of flows (p ≈ 2.5) are used here.…”
Section: Multi-scale Flow and Its Stagnation Point Structurementioning
confidence: 58%
See 2 more Smart Citations
“…[6] showed that the number density n s of stagnation points is a power-law function of the outer to inner length-scale ratio L/η, n s = C s L −d (L/η) Ds where the fractal dimension D s is such that p + 2D s /d = 3 and d=2, 3 for 2D, 3D turbulence. [13] generated a Q2D multi-scale laminar flow with an imposed multi-scale spatial distribution of stagnation points and corroborated that such a flow has a powerlaw energy spectrum in agreement with p + D s = 3. The same rig and family of flows (p ≈ 2.5) are used here.…”
Section: Multi-scale Flow and Its Stagnation Point Structurementioning
confidence: 58%
“…This leads to a measurement grid containing 287x287 velocity vectors. For full details on the rig and experiments, see [13] who also show that the flow at the free surface of the brine is Q2D.…”
Section: Multi-scale Flow and Its Stagnation Point Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Different generic setups, including 2-and 3-magnet configurations with different orientations with respect to the imposed electric DC currents, were analysed. In contrast to the previously mentioned studies, of Honji et al [16] and Rossi et al [40,41], Verdoold et al [45] applied electric currents that were sufficiently strong (up to I = 10 A) to locally create transient and turbulent flow regimes. Experimental studies were based on dye visualisations similar to that presented in Honji et al [16], but without velocity measurements.…”
Section: Electromagnetically-driven Flowsmentioning
confidence: 97%
“…Rossi et al [40,41] addressed electromagnetically driven steady quasi-two-dimensional laminar flows with multi-scale point topology. The authors introduced an interesting concept of imposed electromagnetic forcing originating from the fractal-structure based geometry of the permanent magnets with opposite polarities.…”
Section: Electromagnetically-driven Flowsmentioning
confidence: 99%